Lipid rafts and their roles in T-cell activation - Horejsí, Václav (Microbes and infection, 2005)
Lipid rafts are defined as detergent-resistant membrane microdomains of specific lipid and protein composition. They are involved in many aspects of cell biology, including T-cell activation and immunoreceptor signaling. This review discusses current controversies around lipid rafts and summarizes recent developments in the area.
Keywords: receptory antigenů T-buněk; Signal Transduction; Humans; Lymphocyte Activation; aktivace lymfocytů; lidé; Membrane Microdomains; T-Lymphocytes; Receptors, Antigen, T-Cell; membránové mikrodomény; signální transdukce; T-lymfocyty